Kelayakan Lembar Kerja Peserta Didik Berbasis Liveworksheet Pada Pembelajaran Tema 3 Subtema 2 Kelas IV SD Negeri 01 Jagoi Babang - Burgawanti Burgawanti; Kartono Kartono; Dyoty Auliya Vilda Ghasya; Hery Kresnadi; Suparjan Suparjan (Departement of Mathematics Education, 2023)
This study aims to produce LKPD products based on the livework sheet application in learning theme 3 (caring for living things) sub-theme 2 (diversity of living things. a proper and practical environment to be used for fourth grade students at SD Negeri 01 Jagoi Babang. This research uses a Research approach and Development (R&D) with the ADDIE model which consists of five stages (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques in this study used questionnaires and interviews. The research instruments used were validation questionnaire sheets, student response sheets, and interview.The sample of this study were 15 students in grade IV consisting of 6. women and 9. men. Data analysis, in this study used qualitative data and quantitative data, qualitative data obtained based on responses in the form of comments and suggestions, while quantitative data, in the form of score results validation of material experts. The results showed that the developed product obtained an average percentage based on material experts of 88.33% (very feasible) and practicality with an average percentage of 77.47% in the practical category. Products developed can support teachers in the learning process in class.